Artificially constructed collagen-targeting receptors on mesenchymal stromal cells promote anoikis resistance and tissue repair - Yinghui Xu; Yuanhao Chen; Yilin Wang; Ze Yang; Yating Ruan; Jianzheng Li; Yuqiao Huang; Xinliang Ming; Jing Zhao; Ying Zhang; Zhi Fang; Changchen Xiao; et al. (Proceedings of the National Academy of Sciences, 2026)
Mesenchymal stem cell (MSC)-based therapy holds significant promise in regenerative medicine, leveraging their multipotent differentiation capacity and paracrine effects. However, clinical translation is limited by poor cell survival and engraftment in a hostile injury microenvironment, where detachment-induced anoikis and insufficient extracellular matrix (ECM) adhesion compromise their therapeutic efficacy. Here, we engineered MSCs with surface-anchored von Willebrand factor A3 domain (vWF A3), a natural collagen-binding domain with exceptional affinity for type I and III collagen, to simultaneously confer collagen-targeting and prosurvival functionalities. The vWF A3-modified MSCs (vWF A3-MSCs) exhibited enhanced collagen-binding capacity, improving retention in myocardial infarction (MI) and osteoarthritis (OA) lesions. Beyond adhesion, vWF A3-MSCs demonstrated improved reparative capacity and anoikis resistance, driven by the activation of ECM–receptor interaction and integrin β3 signaling. These modifications promoted proangiogenic effects via mitogen-activated protein kinase pathway activation while enhancing cell survival through Hippo pathway suppression. In vivo studies confirmed the superior therapeutic efficacy of vWF A3-MSCs in both MI and OA models, highlighting how the artificially constructed collagen-targeting receptors on cell and ECM-adhesion-targeted strategy reprogram cellular fate and enhance therapeutic efficacy in stem cell–based regenerative medicine.